Exploring Lutzomyia longipalpis Sand Fly Vector Competence for Leishmania major Parasites - Cecílio, Pedro (J Infect Dis, 2020)
Lutzomyia longipalpis sand flies are the major natural vector of Leishmania infantum parasites, responsible for transmission of visceral leishmaniasis in the New World. Several experimental studies have demonstrated the ability of Lu. longipalpis to sustain development of different Leishmania species. However, no study had explored in depth the potential vector competence of Lu. longipalpis for Leishmania species other than L. infantum. Here, we show that Lu. longipalpis is a competent vector of L. major parasites, being able to acquire parasites from active cutaneous leishmaniasis lesions, sustain mature infections, and transmit them to naive hosts, causing disease.